Tuneable photonic crystals obtained by liquid crystal infiltration - Kitzerow, Heinz-Siegfried; Lorenz, A.; Matthias, H. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Dichroic photo- and electroluminescence of oligo p-(phenylene vinylene) derivatives - Lauhof, Marcus W.; Benning, Stephan A.; Kitzerow, Heinz-Siegfried; Vill, Volkmar; Scheliga, Felix; Thorn-Csányi, Emma (Synthetic Metals)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Coherent digital polarization diversity receiver for real-time polarization-multiplexed QPSK transmission at 2.8 Gb/s - Pfau, Timo; Peveling, Ralf; Hauden, Jerome; Grossard, Nicolas; Porte, Henri; Achiam, Yaakov; Hoffmann, Sebastian; Ibrahim, Selwan K.; Adamczyk, Olaf; Bhandare, Suhas; Sandel, David; Porrmann, Mario; et al. (IEEE PHOTONICS TECHNOLOGY LETTERS)

PDL-tolerant real-time polarization-multiplexed QPSK transmission with digital coherent polarization diversity receiver - Pfau, T.; Peveling, R.; Hoffinann, S.; Bhandarel, S.; Ibrahim, S.; Sandel, D.; Adamczyk, O.; Porrmann, M.; Noé, Reinhold; Achiam, Y.; Schlieder, D.; Koslovsky, A.; et al. (2007 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

Distributed PMD compensator in Lithium-Niobate-Tantalate: Performance Modeling toward highest bit rates - Bhandare, Suhas; Noé, Reinhold (JOURNAL OF LIGHTWAVE TECHNOLOGY)

100 km fiber span in 292 km, 2.38 Tb/s (16 x 160 Gb/s) WDM DQPSK polarization division multiplex transmission experiment without Raman amplification - Abas, Ahmad Fauzi; Hidayat, Ariya; Sandel, David; Milivojevic, Bijana; Noé, Reinhold (OPTICAL FIBER TECHNOLOGY)

Realtime optical synchronous QPSK transmission with DFB lasers - Pfau, T.; Adamezyk, O.; Herath, V.; Peveling, R.; Hoffmann, S.; Porrmann, M.; Noé, Reinhold (2007 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

Real-time digital carrier & data recovery for a synchronous optical quadrature phase shift keying transmission system - Noé, Reinhold; Pfau, Timo; Adamczyk, Olaf; Peveling, Ralf; Herath, Vijitha; Hoffmann, Sebastian; Porrmann, Mario; Ibrahim, Selwan K.; Bhandare, Suhas (2007 IEEE/MTT-S INTERNATIONAL MICROWAVE SYMPOSIUM DIGEST, VOLS 1-6)

Liquid crystal director fields in micropores of photonic crystals - Matthias, Heinrich; Schweizer, Stefan L; Wehrspohn, Ralf B; Kitzerow, Heinz-Siegfried (Journal of Optics A: Pure and Applied Optics)
Keywords: Atomic and Molecular Physics; and Optics

Real-time Digital Carrier & Data Recovery for a Synchronous Optical Quadrature Phase Shift Keying Transmission System - Noé, Reinhold; Pfau, Timo; Adamczyk, Olaf; Peveling, Ralf; Herath, Vijitha; Hoffmann, Sebastian; Porrmann, Mario; Ibrahim, Selwan K.; Bhandare, Suhas (2007 IEEE/MTT-S International Microwave Symposium)

Distributed PMD Compensator in Lithium–Niobate–Tantalate: Performance Modeling Toward Highest Bit Rates - Bhandare, Suhas; Noé, Reinhold (Journal of Lightwave Technology)

Coherent Digital Polarization Diversity Receiver for Real-Time Polarization-Multiplexed QPSK Transmission at 2.8 Gb/s - Pfau, Timo; Peveling, Ralf; Hauden, JÉrÔme; Grossard, Nicolas; Porte, Henri; Achiam, Yaakov; Hoffmann, Sebastian; Ibrahim, Selwan K.; Adamczyk, Olaf; Bhandare, Suhas; Sandel, David; Porrmann, Mario; et al. (IEEE Photonics Technology Letters)

Kastrat - Grotjahn, Rebecca (Enzyklopädie der Neuzeit Bd. 6)

Das Elend der Sozialen Arbeit – Die „neue Unterschicht“ und die Schwächung des Sozialen - Heite, Catrin; Klein, Alex; Landhäußer, Sandra; Ziegler, Holger (Erziehung zur Armut? Soziale Arbeit und die ‚neue Unterschicht’)
Die 'neue Unterschicht' ist entdeckt und die Erziehung dieser prekarisierten Gesellschaftsmitglieder wird gefordert. FachexpertInnen aus Erziehungswissenschaft und Sozialpädagogik gehen in diesem Band der Frage nach, wie angemessen eine solche Diagnose der 'neuen Unterschicht' und der damit verbundene Therapievorschlag einer Erziehung zur Armut ist: Wie wird hier soziale Ungleichheit in einer veränderten Form zum Gegenstand? Welche Herausforderungen sind damit für die Soziale Arbeit verbunden? Hält die Diagnose einer 'neuen Unterschicht' einer empirischen Überprüfung stand? In welcher Weise werden hier bestimmte Bevölkerungsgruppen zum Zielpunkt politischer Strategien? Die Beantwortung dieser Fragen macht das Spannungsverhältnis struktureller, kultureller und moralischer Erklärungsversuche mit Blick auf eine fachliche und politische Verortung Sozialer Arbeit analysierbar.
Keywords: Bildung Gesellschaft Moral Soziale Arbeit Sozialpädagogik Sozialstaat Unterschicht neue Unterschicht

"Antlitz der Zeit". Zur soziologisch-politischen Dimension des Physiognomischen in der Ära der Neuen Sachlichkeit - Öhlschläger, Claudia (Die Souveränität der Literatur. Zum Totalitären der Klassischen Moderne 1900-1933)

Middleware for Secure Home Access and Control - Marin, Andres; Müller, Wolfgang; Schäfer, Robbie; Almenarez, Florina; Diaz, Daniel; Ziegler, Max (Proc. of the IEEE PerCom Middleware Support for Pervasive Computing (PerWare 2007))
User adaptive systems in the context of pervasive computing can only unveil their power if based on a generic middleware managing private data and context information in combination with flexible device access and control. However, managing those data poses severe privacy problems both legally and from a trust perspective. Therefore we propose a home automation middleware for secure management of user and context data that gives access to services just for the authorized users and devices. The middleware has been successfully tested at the ambient computing (AC-LAB) at the University of Paderborn.

Device Independent User Interfaces for Smart Cards - Schäfer, Robbie; Müller, Wolfgang; Marin-López, Andrés; Díaz-Sánchez, Daniel (Proceedings of the 9th International Conference on Human Computer Interaction with Mobile Devices and Services (MobileHCI2007))
Smart Cards are becoming a ubiquitous means for securing a wide range of interactive applications. However in many cases its use is limited for authentication purposes only. In this paper we extend the use of smart cards for carrying abstract user interface descriptions which can be rendered on different and potentially remote clients that in addition can support different interaction modalities. This adds on the one hand to the security since a backend application cannot be used without the UI description, and on the other hand to the versatility of applications, since all devices with a respective renderer for certain modalities can be utilized.
Keywords: Smart Card; Abstract User Interface; Device Independence

A Low-Cost Positioning System for Location-Aware Applications in Smart Homes - Schäfer, Robbie; Müller, Wolfgang; Deimann, Roman; Kleinjohann, Bernd (Proceedings of the Workshop on Mobile Spatial Interaction at CHI 2007)
Location-aware services for private use such as GPS- based navigation systems and GSM-based offerings have become quite a success for outdoor applications, while indoor positioning systems are still mainly employed for professional use only. The main reasons are cost issues and the complexity of setup and maintenance of those systems. In this paper we present CaMPTrack (Camera-based Multiple Person Tracker), a prototype of a webcam-based positioning system and discuss its application and development challenges.
Keywords: Positioning Systems; Camera Based; Cost Efficiency; Smart Home Applications

Evaluation of a Multimodal System Based on Dialogue Models and Transformations International Workshop on Usability of User Interfaces: From Monomodal to Multimodal - Schäfer, Robbie; Müller, Wolfgang (Proceedings of IWUMUI’2007 at HCI'2007)

Tuneable photonic crystals obtained by liquid crystal infiltration - Kitzerow, Heinz-Siegfried; Lorenz, A.; Matthias, H. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials